European identity and multilingualism - Velički, Damir (Revija za elementarno izobraževanje, 2020)
In the official documents that regulate certain segments of education in Croatia, the terms Europe and European (identity) appear. In this paper the authors analyse the concept of European identity and reach the conclusion that it has not been unambiguously defined. The term European identity is closely connected within the European Union with multilingualism. Through a policy of multilingualism, the European Union strives to preserve language diversity in Europe. The authors of this paper start from the question of whether foreign language learning increases the feeling of being connected to Europe and present the results of a study that was conducted at the Faculty of Teacher Education in Zagreb in 2018/19.
Keywords: environment; learning; learning ffectiveness; okolje; spremenljivke; students; učenci; učenje; učna učinkovitost; variables